Externalities, location, and regional development: Evidence from German district data - Thiess Büttner (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1997)
Local productivity externalities play an important role in the recent literature on economic geography and regional growth. But apart from case studies there is only weak empirical evidence. Using a simple theoretic framework the paper derives two empirical implications of those externalities which are applied to district level data for German manufacturing industries. Although important regional concentration is found, significant correlation with local demand renders it difficult to draw conclusions. Yet, the importance of local externalities is supported by the long-run development of single industries, as the extent of general manufacturing activities represented by employment and the number of establishments has positive effects on growth.This result is confirmed from an analysis of regional establishment growth, and is finally shown to be consistent with the aggregate development in manufacturing employment.
Keywords: 330; Regionale Entwicklung; Agglomerationseffekt; Regionaler Arbeitsmarkt; Industrie; Deutschland